Implementation, Challenges, and Opportunities of the Special Program for Employment of Students (SPES) in a First-Class Province in Central Philippines: A Mixed Method Sequential Inquiry - Bachita, Elma; Caelian, Merlita V. (Technium Social Sciences Journal, 2025)
This study evaluated the implementation of the Special Program for Employment of Students (SPES) by Public Employment Service Offices (PESOs) in selected local government units (LGUs) within a first-class province. Focusing on youth employment, the research aimed to empower students, bridge the education-employment gap, and foster economic mobility. An explanatory sequential mixed-methods design was employed, integrating quantitative and qualitative data. Phase 1 involved quantitative analysis of survey responses. Phase 2 utilized semi-structured interviews based on quantitative findings, with results integrated and presented through joint themes from the qualitative phase. Respondents included 15 purposively sampled implementers and 238 SPES beneficiaries from the 2021-2022 school year, selected via stratified random sampling. Research instruments, based on RA 10917, underwent validity and reliability testing. Data analysis involved descriptive and inferential statistics, following normality testing. The quantitative phase revealed a "very great" extent of SPES implementation by PESOs in the province. Both respondent types rated it "very great," and most LGUs with more than 50 beneficiaries also rated it "very great" based on income class and beneficiary count. The qualitative phase corroborated these findings, enriched by beneficiaries' experiences, leading to central themes and sub-themes supported by testimonies. This integration resulted in meta-inferences confirming PESOs' instrumental role in SPES implementation and the program's positive economic and social benefits for beneficiaries and their families. Significant differences in implementation were attributed to LGU income classification and beneficiary numbers. Challenges remain, but substantial opportunities exist for SPES enhancement in LGUs.